Integration of Neurobiology and Spiritual Psychiatry: Mechanisms of Fear Extinction in Ophidiophobia through Analysis of the Story of Prophet Moses - Liko Maryudhiyanto; Indradi Octodhiyanto (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
Ophidiophobia is a specific phobia with strong evolutionary roots that significantly impacts individuals’ quality of life and clinical functioning. Although exposure therapy remains the gold standard treatment, its effectiveness is often limited by patient resistance and high anticipatory anxiety. This study aims to synthesize existing literature on the neurobiological mechanisms underlying snake phobia, identify key morphological triggers, and explore the potential integration of psychospiritual interventions based on the narrative of Prophet Moses. A systematic literature review was conducted following the PRISMA 2020 guidelines, using databases such as PubMed, Scopus, and Google Scholar for publications between 2015 and 2025. Study quality was assessed using the JBI Critical Appraisal Tools. The findings indicate that the human brain possesses a visual detection system highly sensitive to specific scale patterns and curvilinear shapes, triggering rapid responses via the amygdala pathway. Exposure therapy facilitates fear extinction through neuroplastic processes involving prefrontal regulation. The integration of religious narratives may support cognitive reappraisal as a complementary approach. This study proposes an integrative framework to enhance culturally adaptive therapeutic strategies.